Urbanization Process of the San Antonio neighborhood in Puebla city - González Márquez, Eliana Pilar (Benemérita Universidad Autónoma de Puebla, 2021)
In this article, the urbanization process of a founding neighborhood of the city of Puebla isexposed as part of the research results of the master's degree in Sociocultural Anthropologyof the author. San Antonio was a neighborhood originally destined for the indigenouspopulation that lived in the city, later for workers in the boom of the textile industry and iscurrently a neighborhood that is part of the heritage zone of the historic center of the city.In this article I present a historical tour of the city and the neighborhood of San Antoniobased on the construction of biographical accounts of residents of the neighborhood anddocuments from the Municipal Archive that give an account of the urban processesexperienced in the historic center during the period of expansion and growth of the city ofPuebla.